The Effectiveness of Wordwall Media in Improving Elementary School Students’ Reading Skills - Susilo, Jimat; AshShoffat, Qoulan Sadida; Haryati, Efry; Kristiayuniar, Tami; Mudopar, Mudopar (Universitas Pendidikan Mandalika, 2025)
Reading skills are one of the language skills that are closely related to other language skills. In fact, reading skills have a strong influence on writing skills. The problem that arises is that there are still many elementary school students who cannot read fluently due to a lack of reading ability. This study aims to pilot wordwall media in order to improve the reading ability of elementary school students. Wardwall media is a type of game that is allegedly able to improve the reading ability of elementary school students. This research is a type of classroom action research that is carried out in two learning cycles. The research was carried out on grade VI students of SD Negeri Tunas Karya. An instrument used to measure students' reading ability through a reading test. Some aspects used as guidelines for assessing the reading ability of elementary school students include (1) reading ability, (2) understanding of reading content, and (3) fluency in reading. Based on the results of the study obtained through two cycles, it shows that students' reading ability has improved This can be seen from the observation and work of the student group that has improved, where in the first cycle, the average observation score is 59%. The average test score was 81, while in the second cycle, the average observation score was 89%, and the average test result was 96. Based on these results, it can be said that wordwaal media is effective in improving the reading skills of elementary school students.